Invited Review: The spectrum of neuropathology in COVID‐19. (20th October 2020) - Al‐Sarraj, S.; Troakes, C.; Hanley, B.; Osborn, M.; Richardson, M. P.; Hotopf, M.; Bullmore, E.; Everall, I. P.
Abstract : There is increasing evidence that patients with Coronavirus disease 19 (COVID‐19) present with neurological and psychiatric symptoms. Anosmia, hypogeusia, headache, nausea and altered consciousness are commonly described, although there are emerging clinical reports of more serious and specific conditions such as acute cerebrovascular accident, encephalitis and demyelinating disease. Whether these presentations are directly due to viral invasion of the central nervous system (CNS) or caused by indirect mechanisms has yet to be established. Neuropathological examination of brain tissue at autopsy will be essential to establish the neuro‐invasive potential of the SARS‐CoV‐2 virus but, to date, there have been few detailed studies. The pathological changes in the brain probably represent a combination of direct cytopathic effects mediated by SARS‐CoV‐2 replication or indirect effects due to respiratory failure, injurious cytokine reaction, reduced immune response and cerebrovascular accidents induced by viral infection. Further large‐scale molecular and cellular investigations are warranted to clarify the neuropathological correlates of the neurological and psychiatric features seen clinically in COVID‐19. In this review, we summarize the current reports of neuropathological examination in COVID‐19 patients, in addition to our own experience, and discuss their contribution to the understanding of CNS involvement in this disease.